Turning the Invasive Alien Species Challenges into Local Opportunities: A Case Study of the Enclave Villages in Bromo Tengger Semeru National Park - Santosa, Endratno Budi; Nindyasari (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Apart from its adverse impact on biodiversity in an ecosystem, the presence of Invasive Alien Species (IAS) can be a blessing in disguise for local communities. Its daily utilization, including for traditional medicine needs, is a crucial factor in how the existence of Invasive Alien Species can be a game changer for the local community. This research took place in a national park, Bromo-Tengger-Semeru, Indonesia, and focuses on an enclave village inhabited by the indigenous Tengger people. It aimed to evaluate how the presence of Invasive Alien Species, specifically fennel (Foeniculum vulgare) and slimmer weed or kirinyuh (Chromolaena odorata), has adverse impacts on the natural environment but potentially has positive impacts on the community’s socio-economy. The research was conducted through a literature study referring to a semi-structural literature review based on the Scopus database and descriptive analysis based on the interviews with various key informants, which included the national park management, local government at the village and sub-district levels, NGO representatives, and community group who understand and directly utilize IAS plants. The results showed that based on the literature review, research on IAS, especially Fennel and slam weed, is still very limited. Those two species have embedded connections with the locals. In addition to its economic potential, utilizing IAS plants for traditional medicine and ritual completeness for local communities is a critical factor that makes its existence need to be better managed. At this point, a more integrative alternative management of the area was proposed as the way forward.